Pengaruh Upah Minimum Terhadap Penyerapan Tenaga Kerja Bidang Industri Di Indonesia - Susilowati, Lina; Wahyuni, Dwi (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2019)
The minimum wages policy in Indonesia raises many pros and cons. This is due to increasing the minimum wage will have an impact on increasing the income of workers, at the same time an increase in the minimum wage adds to the burden of costs on employers. Some studies saw that increasing minimum wages policy can increase employment while other studies saw e opposite results. This study aimed to analyze the effect of minimum wages on employment in the industrial sector in Indonesia for the period 2012-2017.This study used a control variable from the supply side namely the labor force and used a quantitative approach using panel regression analysis techniques with 6 year time series data for the 2012-2017 period combined with 33 province cross section data. The results showed that the minimum wage had a negative effect on employment in the industrial sector in Indonesia for the period 2012-2017. Whereas the labor force control variable has a positive influence on employment.